A dissertation by Zygmunt Gloger Czy lud polski jeszcze śpiewa? [Does the Polish folk still sing?] (1905) a question about understanding of tradition, community and good remembrance12 - Józefowicz, Anna (Kultura-Społeczeństwo-Edukacja, 2020)
Józefowicz Anna, A dissertation by Zygmunt Gloger Czy lud polski jeszcze śpiewa? [Does the Polish folk still sing?] (1905) a question about understanding of tradition, community and good remembrance. Culture – Society – Education no 2(16) 2019, Poznań 2019, pp. 149–162, Adam Mickiewicz University Press. ISSN 2300-0422. DOI 10.14746/kse.2019.16.10. The question contained in the title of the dissertation of the great folklore, researcher of the past, a lover of sightseeing trips – Zygmunt Gloger Czy lud polski jeszcze śpiewa? [Does the Polish folk still sing?] was asked, far more than a hundred years ago. It was put to Gloger by a French musician and journalist who was staying in Poland in 1901 to celebrate the opening of the Warsaw Philharmonic. He asked this way, because he was fascinated with music pieces he had heard on the stage, based “on beautiful folk motifs”. Small size, because only 24-page Gloger’s dissertation issue in 1905 is an attempt to answer the problem raised in the title. Above all, the dissertation is an expression of Gloger’s regret over the changes that took place in contemporary culture, namely forgetting the role of the song for the Slav community. This is way the author knew the achievements of this community, he devoted his whole life to saving them, he could not understand how contemporary intelligentsia did not see the need for protection, as he described it “our ancient, native and indigenously Slavicnational song and music”. This text is an attempt to analyze Gloger’s essay Czy lud polski jeszcze śpiewa? [Does the Polish folk still sing?], extracting and developing the main theses contained in it, as well as noticing their value today, not forgetting the circumstances of creating the text over 100 years ago.